SPRAWIEDLIWOŚĆ JAKO KRYTERIUM OCENY SYSTEMU EKONOMICZNO-POLITYCZNEGO - Skarżyńska, Krystyna (Civitas et Lex, 2015)
Justice is a widely used evaluation criterion applied to both particular decisions and behaviours as well as to whole social, economic and political systems. The paper presents research results from the representative sample of adult Poles conducted in September 2014. The goal of the research was to investigate the relationships between different schemata of world perception and the evaluation of the justice of the current socio-economic system. The method of the data collection was computer assisted telephone interviews. The results indicate that the evaluations of justice of the political system are lower when: political cynicism is higher, interpersonal distrust is higher and when respondents held a stronger belief that the social world is full of uncontrollable danger. Also the lower evaluations of justice of the current system were accompanied by acceptance of aggression in politics. Socio-demographic variables were less correlated with the evaluations of the justice of the system then were psychological variables. Only age and educational level significantly but weakly differentiated the evaluations of justice.